2010
DOI: 10.1007/s12199-010-0198-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cigarette smoking on plasma uric acid concentrations

Abstract: Objectives The purpose of this study was to examine the effect of cigarette smoking on plasma uric acid concentration and to determine the correlation between this parameter and the biological tobacco markers, plasma thiocyanate and urinary cotinine. Methods The initial study was conducted on 300 subjects; 138 of them were nonsmokers (62 men and 76 women) aged 14-72 years and 162 were current smokers (145 men and 17 women) aged 16-85 years. Uric acid, creatinine, and urinary cotinine were determined by the enz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
64
4
4

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(77 citation statements)
references
References 24 publications
5
64
4
4
Order By: Relevance
“…In this study, we analyzed that the current smokers were divided into two groups (mild and heavy). Several other studies also reported a significant negative correlation between serum uric acid level and the smoking status including the average number of cigarettes smoked per day and the smoking duration (Haj Mouhamed et al, 2011;Slater et al, 1985). In the present study, we also used pack-years as a chronic parameter.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…In this study, we analyzed that the current smokers were divided into two groups (mild and heavy). Several other studies also reported a significant negative correlation between serum uric acid level and the smoking status including the average number of cigarettes smoked per day and the smoking duration (Haj Mouhamed et al, 2011;Slater et al, 1985). In the present study, we also used pack-years as a chronic parameter.…”
Section: Discussionmentioning
confidence: 87%
“…Some studies reported a significant negative correlation between serum uric acid level and the smoking status (Haj Mouhamed et al, 2011;Slater et al, 1985). Obesity factor which can be assessed by waist circumference (WC) is also positively associated with the occurrence of cardiovascular events and diastolic dysfunction (Czernichow et al, 2005).…”
Section: Measuring Pulse Wave Velocity (Pwv) Is a Noninvasivementioning
confidence: 99%
“…Although conventional factors, including age, body mass index (BMI), alcohol consumption and cigarette smoking, contribute greatly to variations in SUA concentrations [27], genetic determinants also play roles, and heritability as high as 42% have been reported [28]. Moreover, genetic studies facilitate the development of effective treatments for associated diseases.…”
Section: Genetic Predisposition To Hyperuricemiamentioning
confidence: 99%
“…In the majority of gout patients, hyperuricemia occurs as a result of overproduction of uric acid (UA) or impaired excretion of renal UA (Terkeltaub et al, 2006). Previous studies have indicated that conventional risk factors including age, body mass index, cigarette smoking, and alcohol intake can influence serum UA concentration (Heinig and Johnson, 2006;Brandstätter et al, 2008;Haj Mouhamed et al, 2011). Moreover, serum UA levels are also determined by genetic factors, with heritability ranging from 25 to 63% (Yang et al, 2005;Doherty, 2009).…”
Section: Introductionmentioning
confidence: 99%